Change the habit to change the practice: Do audits really ever change anything?. Issue 9 (September 2017) - Bodansky, D.; Oskrochi, Y.; Judah, G.; Lewis, M.; Fischer, B.; Narayan, B.
Abstract: Introduction: Methicillin resistant staphylococcus aureus (MRSA) eradication by nurses and pre-op induction antibiotics are mandated for emergency surgery, where true status is unknown. We assessed adherence to local MRSA guidelines for patients undergoing emergency hip fracture surgery and employed point of decision prompts to influence clinicians' behaviour. Methods: We undertook a retrospective record review for all patients undergoing emergency hip fracture surgery at a UK major trauma centre over 3-months. Demographics, MRSA eradication therapy and antibiotics were recorded. Admission-to-MRSA swab result time was compared to the admit-to-operation time. Posters on induction antibiotics were placed in anaesthetic rooms, stickers on MRSA eradication therapy on nursing care bundles and standards re-audited after 6 months. Results: The case-mix was similar in both audit cycles: initial audit (n = 69, mean age 76.9, range 33–94), re-audit (n = 77, mean age 73.8, range 18–95). There was a small rise in adherence to eradication therapy prescription (1% vs 8%) after sticker distribution, although compliance was poor pre and post intervention. Correct antibiotic choice for MRSA unknown patients (18% vs 94%) improved significantly after poster intervention. Operations occurred at a median of 24.05 h (Q1 17.6, Q3 32.3) from admission but MRSA swab results returned at a median of 48 h (Q1 41.5, Q3 59.5) p = <0.0001. Conclusion: Providing reminders at the points where decisions are to be made are effective. Audit interventions should be easily undertaken and will become habitual if connected in sequence to old behaviours.